Epigenomic programming contributes to the genomic drift evolution of the F-Box protein superfamily in Arabidopsis - Hua, Zhihua (National Academy of Sciences, 2013)
Comparisons within expanding sequence databases have revealed a dynamic interplay among genomic and epigenomic forces in driving plant evolution. Such forces are especially obvious within the F-Box (FBX) superfamily, one of the largest and most polymorphic gene families in land plants, where its frequent lineage-specific expansions and contractions provide an excellent model to assess how genetic variation impacted gene function before and after speciation. Previous phylogenetic comparisons based on orthology, diversity, and expression patterns identified three plant FBX groups—Common, Lineage-Specific, and Pseudo(genized)—whose emergences are consistent with genomic drift evolution. Here, we examined this variance within Arabidopsis thaliana by evaluating SNPs for all 877 FBX loci from 432 naturally occurring accessions and their relationships to variations in natural selection, expression, and DNA/histone methylation. In line with their phenotypic importance, Common FBX loci have low polymorphism but high deleterious mutation rates indicative of stringent functional constraints. In contrast, the Lineage-Specific and Pseudo groups are enriched in genes with basal expression and higher SNP density and more correlated with methylation marks (RNA-directed DNA methylation and histone H3K27 trimethylation) that promote transcriptional silencing. Taken together, we propose that reversible epigenomic modifications helped shape FBX gene evolution by transcriptionally suppressing the adverse effects of gene dosage imbalance and harmful FBX alleles that arise during genomic drift, while simultaneously allowing innovations to emerge through epigenomic reprogramming.